Analisis Pertumbuhan Dan Kontribusi Pajak Daerah, Retribusi Daerah, Dan Lain-Lain Pad Yang Sah Terhadap Pendapatan Asli Daerah (Studi Pada Kabupaten/Kota Di Provinsi Jawa Tengah) - Syafitri, Dhyni Inka, Dra. Mujiyati, M.Si (2016)
This study aims to determine the level of growth and the contribution of local taxes, levies, and other legitimate PAD on revenue. Data collection is done by the method of documentation. The analytical method used in this research is quantitative descriptive analysis method by calculating the effectiveness ratio, the ratio of the growth rate and the ratio of contribution of local taxes, levies, and other legitimate PAD. The results showed Based effectiveness ratio of the average tax, retribution, and other legitimate PAD highly effective for three years local taxes, levies, and other legitimate PAD has the effectiveness of more than 100%. Based on the results of the calculation of growth rates, the average growth of local taxes in 2011-2013 showed an average of 45.73% with less success criteria, the average growth of -3.53 levies with no success criteria, and Other PAD authorized by 38.53% with less success criteria. Then the local tax contributions to local revenue on average 32.89% with moderate criteria, contribution levies on revenue an average of 23.51% with sufficient criteria, and contributions Other legitimate PAD by revenue on average 39.28% with moderate criteria.